Burnout, Anxiety, Stress, and Depression Among Iranian Nurses: Before and During the First Wave of the COVID-19 Pandemic - Zakeri, Mohammad Ali; Rahiminezhad, Elham; Salehi, Farzaneh; Ganjeh, Hamid; Dehghan, Mahlagha (Frontiers in Psychology, 2021)
Background: Nurses are the major healthcare workforce in an epidemic and have the most contact with patients. Frontline nurses face many health challenges during the COVID-19 epidemic, are directly at risk when treating and caring for COVID-19 patients, and thus experience severe stress and problems in the workplace leading to physical, mental, and social disorders, as well as burnout, anxiety, stress, and depression. The purpose of this study was to compare burnout, anxiety, stress, and depression in nurses before and during the first wave of the COVID-19 pandemic. Methods: This was a cross sectional study. We assessed 266 frontline nurses before and 242 frontline nurses during the first wave of the COVID-19 pandemic with one year apart in 2019 and 2020 (two-stage sampling). The data were collected using demographic questionnaire, Maslach Burnout Questionnaire and Depression, Anxiety and Stress Scale (DASS-21) in public hospitals in Southern Iran. Results: There were no significant differences between groups in subscales of burnout (p > 0.05). Anxiety, stress and depression scores significantly increased during the first wave of the COVID-19 pandemic. compared with before the COVID-19 outbreak (p < 0.05). There were significant differences between groups in level of anxiety (p < 0.001) and stress (p = 0.04). Before the COVID-19 outbreak, burnout predicted 11%, 15% and 13% of the variance of anxiety, stress and depression, respectively. In addition, stress, monthly working hours and shift were variables that predicted 16% of the variance of burnout before COVID-19. Conclusion: The results of the present study showed that burnout during the first wave of the COVID-19 pandemic did not change significantly compared with before COVID-19. Anxiety, stress and depression increased significantly first wave of the COVID-19 pandemic.